Validation of the English Language Pain Sensitivity Questionnaire. Issue 6 (1st November 2013) - Sellers, Alethia Baldwin; Ruscheweyh, Ruth; Kelley, Bernard Joseph; Ness, Timothy J.; Vetter, Thomas R.
Abstract : Background and Objectives: The Pain Sensitivity Questionnaire (PSQ) is predictive of pain-related responses to experimental stimuli in German-speaking individuals. Here, we explored the validation of the English translation of the PSQ (PSQ-E). Methods: One hundred thirty-six patients scheduled to undergo a low back interventional procedure completed the PSQ-E and other questionnaires including the Brief Pain Inventory. Pain ratings on a visual analog scale (VAS) were obtained following 2 standardized injections of subcutaneous lidocaine (VAS 1, infiltration in hand; VAS 2, infiltration of procedural site). The VAS measures were compared with the PSQ-E data and other inventories using linear regression analysis with stepwise selection of variables. Results: The PSQ-E properties were in all respects similar to those of the original German PSQ. VAS 1 magnitude was predicted by PSQ-E-minor ( r = 0.26, P < 0.01). VAS 2 magnitude was predicted by PSQ-E-minor ( r = 0.34, P < 0.001), and the prediction was significantly enhanced by further inclusion of the Brief Pain Inventory interference score (total r = 0.40, P < 0.001). Conclusions: The study demonstrated that a significant correlation exists between the PSQ-E and clinically relevant pain ratings. This study validates the PSQ-E both in terms of measuring pain sensitivity and as possible means of recognizing patients with high pain sensitivity. Defining this subset of patients may have clinical utility in the future.